2006
DOI: 10.1071/wf04008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of ignitions in Mediterranean periurban and rural areas: the case of Catalonia

Abstract: Fire prevention requires a specific treatment subject to the innate characteristics of a territory and to the social interaction that takes place there. The present article deals with very different fire behaviors in two neighboring environments, in which unequal ignitory patterns have been identified. The analyzed environments constitute two prototypes of Mediterranean landscape in the region of Catalonia (Spain). The periurban-fire pattern is identified with the Metropolitan Area of Barcelona. The rural-fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 8 publications
4
32
0
Order By: Relevance
“…This is in concordance with other studies reporting that the proportion of burned areas increases with the distance from roads as a consequence of the lower accessibility by fire fighters (Cardille et al 2001, Vasconcelos et al 2001, Badia-Perpinya & Pallares-Barbera 2006. Other studies in Portugal demonstrated that larger distances impacted the proportion of area burned (Marques et al 2011a) or that ignitions that resulted in large fires occur further away from roads (Romero-Calcerrada et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…This is in concordance with other studies reporting that the proportion of burned areas increases with the distance from roads as a consequence of the lower accessibility by fire fighters (Cardille et al 2001, Vasconcelos et al 2001, Badia-Perpinya & Pallares-Barbera 2006. Other studies in Portugal demonstrated that larger distances impacted the proportion of area burned (Marques et al 2011a) or that ignitions that resulted in large fires occur further away from roads (Romero-Calcerrada et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Arianoutsou, 2001;Curt and Delcros, 2010;Martinez et al 2009;RomeroCalcerrada et al 2010;Wittenberg and Malkinson, 2009;Vasconcelos et al 2001;Vazquez et al 2002). In fact, population density and distance to road networks are the major drivers of ignition risk and recent fire research studies identified the rural-urban interface as the most fire prone areas in Mediterranean countries (Badia-Perpinya and Pallares-Barbera, 2006;Catry et al, 2009;Curt and Delcros, 2010;Moreira et al, 2009).…”
Section: Landscape Changes Have Been Increasing Fire Hazard In the Lamentioning
confidence: 99%
“…Although southern European cities are usually regarded as representative examples of compact, dense and land-saving cities (Paul and Tonts [5]; Kasanko et al [6]; Cakir et al [7]), urban growth especially in the form of discontinuous, low density settlements, was found increasing in recent years [8]. Threatened by exurban development, peri-urban landscapes and, more in general, rural areas surrounding big cities are characterized by a variety of land-use classes, which are reflected in fragmented environments sensitive to fires and soil erosion (Arianoutsou [9]; Allen [10]; Badia-Perpinyà and Pallares-Barbera [11]; Briassouli [12]). Forest fires, especially big fires, are relevant events shaping the ecological fragility of the Mediterranean landscape, altering the structure, composition and diversity of landscapes and determining land degradation in certain environmental conditions with important consequences also for the social and economic local context (Christopoulou et al [13]; Martìnez et al [14]; Moreira et al [15]).…”
Section: Introductionmentioning
confidence: 99%